Case study : the Metro Transportes do Sul Concession & Risk Sharing and Public Financial Compensations - Ferreira, Bruno de Araújo Reais (2015)
Objective: The goal of this study is to provide a case-study on the Metro Transportes do Sul (MTS) Concession trough an analysis of the risk sharing and financial compensations. Over the last 20 years, Portugal has been experiencing a large wave of PPP contracts. Concessions experiencing unbalance risk allocation is a constant problem in important projects and the MTS concession has been the most recent example of it. Renegotiation Agreement, calculation of compensations, traffic forecasts, no connection among bodies and unbalanced risk allocation are some of the reasons for a detailed analysis of this concession project Methodology: This paper is divided in two categories: First, a description of the concession contract, the delays in the MTS concession and the renegotiation process; Secondly, an analysis of the financial compensation from the Government and the Risk Allocation situation. Findings: This paper concludes that due to the inaccurate traffic forecast and the lack of coordination among the different bodies in the concession project there is a strong imbalance in the current risk allocation the Government was bound to be the largest contributor of the MTS concession trough financial compensations to the concessionaire Recommendation: The recommendations to this concession project are ground on the idea of a better management of the concession in general, avoiding Demand risk ex-ante, providing better technical condition for monitoring and controlling and more important, analyses traffic forecast on more solid indicators.